PELATIHAN PENGOLAHAN MINUMAN HERBAL ANTI HIPERTENSI SEBAGAI IDE KEWIRAUSAHAAN DALAM MEWUJUDKAN EKONOMI KREATIF DI WILAYAH RT 05 RW 04 GUNUNG ANYAR SURABAYA - RR Nurul Hidayati; Pinky Pininta Dewi; Alvira Sukmawati Sairan; Aurelsa Rarasninggar Nareswari; Erren Yanvia Novarin; Fitri Yani Husain; Salsabila Salsabila; Moh Syawelul Ihqbal; Nurul Khotimah; Oktafia Mula Sela Putri; Ramadhani Dwi Ayu Andarista; Salsa Osama Wiranti; Suherman Suherman (Bajang Institute, 2023)
After the Covid-19 pandemic had a huge impact on the community, especially in the health and economic sectors, we conducted a survey and data collection in the RT 05 RW 04 Gunung Anyar area, Some of the problems we found were high blood pressure or hypertension problems in public health and we also found some problems in MSME players who are not familiar with marketing using internet networks or digital marketing. With this, we approach with observation methods or observation and data collection in the hope that it can be accepted by the people in the region. We conduct a work program, namely training on antihypertensive herbal drink processing and MSME consultation and MSME consultation. With this work program, we hope to help the community towards health, especially hypertension and MSME actors begin to understand digital marketing or digital marketing through the internet network.